Academic inbreeding: exploring its characteristics and rationale in Japanese universities using a qualitative perspective - Horta, H (2011)
This study analyses why and how academic inbreeding as a recruitment practice continues to prevail in Japan, a country with a mature higher education system, where high rates of academic inbreeding endure in most of the research-oriented universities in spite of several higher education reforms. Based on a qualitative analysis, we disclose three characteristics that lead academics to become inbred at Japanese universities. One characteristic-the adoption of "open recruitment processes" in detriment of "closed recruitment processes"-changed over time, limiting academic inbreeding practices, but two other characteristics remained unchanged over time: the "one university learning experience" and the "concentration of doctoral supervisors at the same university". These latter characteristics represent difficult challenges to be tackled as they are also traditional characteristics of the Japanese higher education system. The research also shows that academic inbreeding practices are a means to assure organizational stability and institutional identity, features perceived as important by Japanese universities. A central challenge for the Japanese universities is then to guarantee these features without needing to rely on academic inbreeding practices to obtain them. However, devising policies to meet this challenge calls for institutional will to change, proactive strategies and time.